The Effect of Cannabis Extract on The Growth of Adipose-Derived Stem Cells in Adult Male Rats - Arman Kamali-Sarvestani; Davood Mehrabani; Ebrahim Hosseini; Sara Hashemi (Fasa University of Medical Sciences, 2020)
Background & Objective: Cannabis is an addictive substance that is a pervasive global problem. Cannabis has many medicinal and psychoactive properties. Adipose-derived mesenchymal stem cells (MSCs) are widely used in tissue engineering and organ transplantation. The aim of this study was to investigate the effect of cannabis on the growth and proliferation of adipose tissue MSCs in rats. Materials & Methods: In this experimental study, MSCs were extracted from the adipose tissue of adult male rats and after culturing and confirming that they are mesenchymal by flow cytometry method by CD34-RPE, CD90-RPE and CD105-RPE conjugated antibodies, in the fourth passage of cell culture, the effect of cannabis toxicity at concentrations of 100 and1000 ng/mL during1to7 days on the growth process of these cells was investigated using MTT. Results: The cells detached from the adipose tissue could completely adhere to the floor of the flask, 24 hours after being transferred to the cell culture flasks. The results of flow cytometry showed that the expression of endothelial surface marker was negative and the expression of MSC markers was positive, which confirmed the basic identity of the extracted cells. The results of MTT also showed a significant increase in cell growth up to the third day and then a significant decrease in the growth of cannabis-treated cells up to the sixth day compared to the control group at P<0.05. Conclusion: The results showed that cannabis has a stimulatory or inhibitory effect on the growth rate of adipose tissue-derived MSCs depending on the duration of use.